2022
DOI: 10.1177/02841851221125109
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of multiparametric ultrasound for peripheral nerve schwannoma

Abstract: Background Ultrasound (US) diagnostic techniques have the advantages of low cost, convenient operation, and high availability. Purpose To explore the diagnostic accuracy of multiparametric US in evaluating signs of peripheral schwannoma. Material and Methods This retrospective case-control study included patients with soft-tissue masses on the limbs (divided into the schwannoma and non-schwannoma groups) between January 2017 and November 2020. US features were compared between the two groups, and receiver oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Ultrasound typically shows a well-defined hypoechoic mass with variable posterior acoustic enhancement (24). An entering and exiting nerve sign and a polar blood supply sign on color doppler flow imaging can be seen (25). Ogata et al reported that several ultrasonographic features including maximum diameter, tumor localization and continuity with the nerve were significantly different between schwannoma and angioleiomyoma (26).…”
Section: Figure 3 Histological Features Of Angioleiomyoma (A) the Tum...mentioning
confidence: 99%
“…Ultrasound typically shows a well-defined hypoechoic mass with variable posterior acoustic enhancement (24). An entering and exiting nerve sign and a polar blood supply sign on color doppler flow imaging can be seen (25). Ogata et al reported that several ultrasonographic features including maximum diameter, tumor localization and continuity with the nerve were significantly different between schwannoma and angioleiomyoma (26).…”
Section: Figure 3 Histological Features Of Angioleiomyoma (A) the Tum...mentioning
confidence: 99%
“…In order to facilitate the work of the sonographer, diagnostic signs have been found such as “regular morphology, cystic degeneration, polar blood supply sign, target sign” that, when simultaneously present, allow the diagnosis with a sensitivity and specificity of 95.24% and 96.08%, respectively 2 …”
Section: Figurementioning
confidence: 99%
“…In order to facilitate the work of the sonographer, diagnostic signs have been found such as "regular morphology, cystic degeneration, polar blood supply sign, target sign" that, when simultaneously present, allow the diagnosis with a sensitivity and specificity of 95.24% and 96.08%, respectively. 2 Today, thanks to the considerable advancement of ultrasound technology, it is also possible to make use of many applications such as SMI (superb microvascular imaging) and 2D SWE (shear wave elastography) [3][4][5] ; they promise to provide increasingly accurate information about vascularity and elasticity, respectively, thus allowing a better definition and easier diagnostic recognition of the lesion.…”
mentioning
confidence: 99%